A late Holocene onset of Aboriginal burning in southeastern Australia - Portenga,EW; Rood,DH; Bishop,P; Bierman,PR (Geology, 2016)
The extent to which Aboriginal Australians used fire to modify their environment has been debated for decades and is generally based on charcoal and pollen records rather than landscape responses to land-use change. Here we investigate the sensitivity of in-situ–produced 10Be, an isotope commonly used in geomorphological contexts, to anthropogenic perturbations in the southeastern Australian Tablelands. Comparing 10Be-derived erosion rates from fluvial sediment (8.7 ± 0.9 mm k.y.–1; 1 standard error, SE; n = 11) and rock outcrops (5.3 ± 1.4 mm k.y.–1; 1 SE; n = 6) confirms that landscape lowering rates integrating over 104–105 yr are consistent with rates previously derived from studies integrating over 104 to >107 yr. We then model an expected 10Be inventory in fluvial sediment if background erosion rates were perturbed by a low-intensity, high-frequency Aboriginal burning regime. When we run the model using the average erosion rate derived from 10Be in fluvial sediment (8.7 mm k.y.–1), measured and modeled 10Be concentrations overlap between ca. 3 ka and 1 ka. Our modeling is consistent with intensified Aboriginal use of fire in the late Holocene, a time when Aboriginal population growth is widely recognized.